2004
DOI: 10.1038/sj.cgt.7700742
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effect of hematopoietic cells carrying the gene of ribonuclease inhibitor

Abstract: Human ribonuclease inhibitor (hRI) is an acid protein with a molecular weight of 50 kDa. It can inhibit the activity of pancreatic RNase (RNase A). Angiogenin (Ang) is a member of the ribonuclease super family. It has 35% identity with RNase A and contains ribonucleolytic activity. The substrate specificity of angiogenin seems, however, to be more restricted than that of the pancreatic RNase. Since Ang is an important angiogenic factor and RI is a highly efficient inhibitor of Ang, it can be hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…These reports are consistent and 23 demonstrate the importance of its activity in inducing cancer proliferation. It is also in line with the previous evidence from inhibition studies, which alluded that RNase activity controls the process of angiogenesis (Wang et al 2005, Fu et al 2005. Thus far, however, the molecular basis of Angiogenin in inducing cell proliferation is unknown and would require further studies to clearly elucidate its molecular mechanism (Gao et al 2007).…”
Section: I) Angiogeninsupporting
confidence: 76%
“…These reports are consistent and 23 demonstrate the importance of its activity in inducing cancer proliferation. It is also in line with the previous evidence from inhibition studies, which alluded that RNase activity controls the process of angiogenesis (Wang et al 2005, Fu et al 2005. Thus far, however, the molecular basis of Angiogenin in inducing cell proliferation is unknown and would require further studies to clearly elucidate its molecular mechanism (Gao et al 2007).…”
Section: I) Angiogeninsupporting
confidence: 76%
“…It has been shown that sialylation of cell surface adhesion molecules correlates with cancerendothelial cell adhesion, proliferation, and angiogenesis (19,37). We observed that RNH1, which inhibits in vivo angiogenesis and tumor growth through angiogenin inhibition (38) and PGK1, which acts as endogenous angiogenesis inhibitor (39), were overexpressed after Lith-O-Asp treatment. Lith-O-Asp dose dependently inhibited tube formation of HUVEC cells, suggesting that Lith-O-Asp may participate in antiangiogenic process through RNH1 and PGK1 expression (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Gene therapy with hematopoietic cells carrying the sequence for hRI diminished the neovascularization of melanomas [22].…”
Section: Introductionmentioning
confidence: 99%